Antibacterial and Post-biofilm Effects of Biosynthesized Copper Oxide Nanoparticles Using Pseudomonas aeruginosa Pyocyanin - Hamed, Amna Emad; Rasheed, Hassan Majeed (Iraqi Journal of Science, 2026)
The increasing resistance of bacteria to conventional antibiotics has driven the search for alternative antimicrobial agents, such as metal nanoparticles. Copper oxide nanoparticles exhibit strong antibacterial and antibiofilm properties due to their high surface-to-volume ratio and reactive oxygen species generation. The biosynthesis of nanoparticles (NPs) using microorganisms offers an eco-friendly and cost-effective approach compared to chemical methods. Pseudomonas aeruginosa, a pathogenic bacterium, produces pyocyanin, a redox-active pigment with metal-reducing properties, which can facilitate the synthesis of CuO NPs. Pyocyanin acts as a stabilizing and reducing agent, enabling the formation of NPs with enhanced biocompatibility and antimicrobial efficacy. The research involves the isolation of P. aeruginosa, extraction of pyocyanin, and subsequent biosynthesis of copper oxide nanoparticles. The findings are expected to provide insights into novel therapeutic strategies for combating resistant bacterial strains, addressing a critical public health need. Samples were collected from Baghdad-Al-Yarmouk Teaching Hospital, Ghazi Al-Hariry Hospital, and Al-Imamein Al-Khadumein Teaching. The copper oxide nanoparticles were synthesized from P. aeruginosa using the biological method and characterized using Atomic Force Microscopy (AFM), Field Emission Scanning Electron Microscopy (FE-SEM), and Energy-dispersive X-ray spectroscopy (EDX). These confirmed that it is a nanoparticle. The antimicrobial efficiency of CuO NPs was determined for Six multidrug-resistant bacterial isolates using a well diffusion assay (WDA). The maximum inhibition zone of P. aeruginosa was 34 mm at a concentration of 500mg/ml of CuO NPs. CuO NPs showed consistent inhibition on all strains. This study aims to assess the effectiveness of copper nanoparticles (CuO NPs) biosynthesized using pyocyanin, as an antibacterial agent and antibiofilm after formation against P. aeruginosa, there is a proportional relationship between the concentration of nanoparticles and their effect on non-planktonic cells within the biofilm texture.